2020
DOI: 10.1371/journal.pntd.0008454
|View full text |Cite
|
Sign up to set email alerts
|

Japanese encephalitis virus infection in non-encephalitic acute febrile illness patients

Abstract: Although Japanese encephalitis virus (JEV) is considered endemic in Indonesia, there are only limited reports of JEV infection from a small number of geographic areas within the country with the majority of these being neuroinvasive disease cases. Here, we report cases of JEV infection in non-encephalitic acute febrile illness patients from Bali, Indonesia. Paired admission (S1) and discharge (S2) serum specimens from 144 acute febrile illness patients (without evidence of acute dengue virus infection) were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…A recent prospective study performed in hospitalized patients with dengue-negative febrile illness in Indonesia found that 6% had serological evidence of recent JEV infection. Thrombocytopenia was common during the acute phase of illness in these non-encephalitic cases (69%) but did not occur as frequently as dengue cases from the same study (92%) [ 87 ].…”
Section: Resultsmentioning
confidence: 99%
“…A recent prospective study performed in hospitalized patients with dengue-negative febrile illness in Indonesia found that 6% had serological evidence of recent JEV infection. Thrombocytopenia was common during the acute phase of illness in these non-encephalitic cases (69%) but did not occur as frequently as dengue cases from the same study (92%) [ 87 ].…”
Section: Resultsmentioning
confidence: 99%
“…Classic transmission cycle of JE virus involves pigs as reservoir or amplifying hosts, while the virus itself is transmitted to humans through mosquito bites, mainly Culex species ( Choe et al, 2018 ; Yun and Lee, 2014 ). Although Indonesia belongs to endemic area of JE, routine screening in individuals presenting with acute encephalitis syndrome has been lacking due to limited data on true prevalence of the disease in many provinces ( Ma'roef et al, 2020 ). Sporadic cases have been reported in a number of areas in the past 20 years, including Bali and several cities in Java and Kalimantan (Borneo) island ( Kari et al, 2006 ; Konishi et al, 2009 ; Liu et al, 2010 ; Maha et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…The most likely source of wind-blown infected mosquitoes into the Tiwi Islands is Indonesia or Timor Leste, although Papua New Guinea cannot be ruled out as a potential source. JEV PLOS NEGLECTED TROPICAL DISEASES is believed to be enzootic in Indonesia, with virus isolations from mosquitoes or serological evidence of infection in pigs found in parts of Java, Bali, Lombok, Flores, West Timor and Papua Province (reviewed in [10,11,66]). A clinical case of JE from Irian Jaya (West Papua) was reported from Timika in 1996 [21], supported by serological evidence of human infection [67].…”
Section: Discussionmentioning
confidence: 99%